2019
DOI: 10.5539/jas.v11n5p334
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extracts of Species of the Genus Campomanesia (Myrtaceae) Affect Biological Characteristics of Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae)

Abstract: Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae) is an insect pest that causes great damage to Brassica cultures. It is necessary to develop alternative control methods, because this pest is resistant to many synthetic insecticides that are harmful to the environment. The objective of this study was to evaluate the effects of aqueous extracts of Campomanesia adamantium, C. guazumifolia, and C. xanthocarpa on the life cycle of P. xylostella. These aqueous extracts were prepared in a concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…A number of studies have been performed to determine the insecticidal potential of botanical oils and extracts of certain species—Myrtaceae [ 21 ], Rubiaceae [ 22 ], Anonnaceae [ 23 , 24 ], Meliaceae, Anacardiaceae [ 24 , 25 ], Apocynaceae [ 26 , 27 ], Sapindaceae and Fabaceae [ 28 ]—and the oil of Rutaceae [ 29 ] on the development and/or oviposition of P. xylostella and, consequently, the occurrence of antibiosis and antixenosis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been performed to determine the insecticidal potential of botanical oils and extracts of certain species—Myrtaceae [ 21 ], Rubiaceae [ 22 ], Anonnaceae [ 23 , 24 ], Meliaceae, Anacardiaceae [ 24 , 25 ], Apocynaceae [ 26 , 27 ], Sapindaceae and Fabaceae [ 28 ]—and the oil of Rutaceae [ 29 ] on the development and/or oviposition of P. xylostella and, consequently, the occurrence of antibiosis and antixenosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the term Myrtaceae appears more significantly because it is the family to which the genus belongs and may also reveal the interest of researchers in the family that houses numerous species of interest in the most diverse areas (Farias et al, 2020). The Campomanesia xanthocarpa species also appears relevantly (34 occurrences, 45 links) linked to words that denote potential biological activities, such as inflammation, oxidative stress, bioactive compounds, obesity, cytokines and nitric oxide Souza et al, 2019). It is noted that the terms related to antioxidant activity are yellow, indicating that they are the most recent research, as well as the term savannah (16 occurrences, 29 links), suggesting a research trend towards biological activity with species from this Brazilian biome.…”
Section: Most Cited Articles and Co-occurrence Relationships Of Abstract Between Authorsmentioning
confidence: 99%
“…Promising plants, such as those in the families Meliaceae, Rutaceae, Asteraceae, Annonaceae, Labiatae and Canellaceae, have chemical compounds with repellent or insecticidal potential, as reported by Jacobson [10]. Studies involving plant extracts with insecticidal properties indicate changes in the biological characteristics of insects, such as mortality [11][12][13] changes in food [14,15] or oviposition [15,16] preferences, deformities, and morphological and physiological transformations of P. xylostella [11,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%